RANCANG BANGUN SOLAR TRACKER SINGLE AXIS BERBASIS ARDUINO UNO - Ngurah Yowana Asta Prawangsa; I Gusti Made Bagus Kurniawan; Ida Bagus Alit Swamardika; I Wayan Arta Wijaya; Lie Jasa; Pratolo Rahardjo; I Putu Elba Duta Nugraha (Program Studi Teknik Elektro UNUD, 2025)
Indonesia has abundant solar energy potential; however, its utilization remains limited due to dependence on fossil fuels and the low efficiency of solar panels caused by static installation systems. To address this issue, this study designed and developed a prototype of an automatic single-axis solar tracker based on Arduino Uno to optimize solar energy absorption. The system is controlled by the Arduino Uno R3 for automatic adjustment of the solar panel position, and the ESP32 is used for real-time monitoring of environmental and electrical parameters. The sensors employed include the BH1750 for light intensity, DHT22 for temperature and humidity, INA219 for voltage and current, and ACS712 for current. Test results indicate that the system is capable of automatically adjusting the solar panel angle, accurately monitoring environmental parameters, and generating stable electrical power for eight hours. Although some instability in current readings was observed when the system operated on battery power, the prototype has proven effective and feasible for further development to enhance the utilization of solar energy.